Potential proton pump inhibitor–related adverse effects. Issue 1 (6th August 2020) - Perry, Issac E.; Sonu, Irene; Scarpignato, Carmelo; Akiyama, Junichi; Hongo, Michio; Vega, Kenneth J.
Abstract: Proton pump inhibitors (PPIs) are one of the most common medications taken by patients worldwide. PPIs are used to treat acid‐related disorders, including gastroesophageal reflux disease, peptic ulcer disease, Helicobacter pylori infection, and nonsteroidal anti‐inflammatory drug/stress ulceration. For some of these diseases, long‐term treatment is necessary. With such prolonged use, concern and investigation into potential adverse effects has increased. In addition, data are available regarding potential anticancer effects of PPIs, especially regarding solid tumors. The aim of this review is to assess the literature on PPIs with regard to common concerns, such as drug–drug interactions, the intestinal microbiome, dementia and central nervous system disease, and osteoporosis, as well as to highlight potential negative and positive impacts of the drug in cancer. Abstract : The aim of this review is to assess the literature on proton pump inhibitors with regard to common concerns such as drug–drug interactions, the intestinal microbiome, dementia and central nervous system disease, and osteoporosis, as well as to highlight potential negative and positive impacts of the drug in cancer.